PENGARUH BEBAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT PLN (PERSERO) AREA SURAKARTA - Sofanul Hidayat, Djumali & Siti Maryam (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
Research conducted at PT PLN (Persero) Area Surakarta discount objectives,among others, to determine the effect of workload and work motivation on employeeperformance, to know is there any influence of workload on employee performance andto know there any influence of work motivation on employee performance. The results ofthis study are expected to provide positive feedback to the management of PT PLN(Persero) so that in the future can be used as a reference and consideration in decisionmaking and also if it can enrich the material and also add information to science. Theresults of this research is the discovery of effect workload and motivation is theindependent variable on the performance of 72,7% based on a test of R2 (determination)with the remaining 27,3% is influenced by other variables not be research in thepreparation of this thesis. For variable influence on the performance of the workloadwith other factors constant found no significant effect positive as evidenced by t-test, pvaluewhere 0,000 < 0,05 of data that is processed through the application of SPSSversion 16.0. For variable work motivation on the performance of the other factorsconstant found no significant effect as evidenced by the positive test results in which thep-value 0,000 < 0,05 conclude that motivation has a significant positive effect onemployee performance.Keywords: workload, work motivation, employee performance